CONSERVATION STRATEGY ANALYSIS IN UPSTREAM WATERSHEAD: CASE STUDY IN CIMANDIRI WATERSHEAD - La Gandri; Sahindomi Bana (Jurnal Ecosolum, 2021)
The calibration result of Tank Model on DTA SPAS Cumucang-Cimandiri by using rainfall data, evapotranspiration and land cover in 2009 shows that the determination coeffient  equal to 0,77 to aktual discharge and model output discharge. Validation results using 2014/2015 datas shows a strong relationship between the actual discharge and the model output discharge with a determination coefficient of 0,805 and generate an average daily discharge value of 1,057 m3sec-1, a maximum discharge value of 6,68 m3sec-1, and minimum discharge value of 0,072 m3sec-1. The Model show the hydrological conditions are in moderate category with KRS value of 93,2238. Based on the analysis of internal and external factors using SWOT analysis, it was found that the management strategy of DTA SPAS Cimuncang-Cimandiri was in the SO position (Quadran I).  The conservation strategy is to keep the forest area in a state of > 30% and optimize environmental funds and services to foster people's creativity to improve welfare. As an alternative strategy that can be applied to keep the DTA SPAS Cimuncang-Cimandiri remains in  good conditions  is to make efforts of soil and water conservation such as absorption wells on settlements and making terraces on rice fields. The implementation of this conservation strategy can reduce the value of KRS to obtain of 54,326.